Confucius, Rawls, and the Sense of Justice - Cline, Erin M. (Book collections on Project MUSE., 2013)
This text compares the role of a sense of justice in the ethical and political thought of Confucius and John Rawls. The author demonstrates that the Analects and Rawls's work intersect in an emphasis of the importance of developing a sense of justice.